Coastal Garbage Patches: Fronts Accumulate Plastic Films at Ashmore Reef Marine Park (Pulau Pasir), Australia - Hajbane, Sara; Calmanovici, Bruna; Reisser, Julia; Jolly, Adam; Summers, Vyvyan; Ferrari, Francesco; Ghadouani, Anas; Pattiaratchi, Charitha (Frontiers in Marine Science, 2021)
Millions of tons of buoyant plastic materials enter oceans annually, the majority originating from terrestrial sources and transported to oceans where oceanographic processes disperse or accumulate them. Some of these materials beach while others accumulate in convergent zones in coastal seas and the open ocean. Although accumulations associated with subtropical gyres, for example, the “Great Pacific Garbage Patch” (GPGP) are well-known, coastal accumulation zones have received less attention. Here we report quantities and characteristics of plastics accumulated in fronts encountered within the Ashmore Reef marine park (Pulau Pasir), northern Australia. These areas, as well as surrounding waters, were sampled using Manta trawls, drone, and snorkel surveys conducted in October 2018. With mean plastic concentrations of 523,146 pieces km−2 for plastics > 500 micron these hotpots contained plastic concentrations an order of magnitude higher than surrounding waters (16,561 pieces km−2) and comparable to the largest known accumulation zone: the GPGP. Furthermore, the mean mass within hotspots was 5,161 g km–2 vs. 9 g km–2 in surrounding waters. Therefore, we classify the features described in this study as types of “Coastal Garbage Patches” (CGPs). Importantly, the coastal fronts accumulating plastics in CGPs are key habitats for many marine species. Biomass outnumbered plastics by weight, with a ratio of 0.521 in CGPs and 0.016 in surrounding waters vs. 287.7 recorded in the GPGP. Polymer types found between the CGPs and GPGP were similar, but plastic films vastly dominated in the CGPs, whilst they were amongst the rarest types found in the GPGP. This study demonstrates the existence of CGPs coinciding with high priority conservation zones in coastal waters and highlights a need for further research into these environments.